Performance and meaning in the Quilombo do Rio das Rãs band's DVD (Per Musi, 2022)
The text object it is the relationship between performance and production of meaning in the performance of Banda Quilombo do Rio das Rãs - held in 2009 - at Bom Jesus da Lapa (state of Bahia, Brazil). The analysis was based on the rules of performance (Zumthor 2014), having as reference time and place of performance, purpose of the communicational act, musicians' actions and audience profile. The protagonist of the performative action it is the quilombola subject, who made Music as a mean to get out of his usual condition, marked by exclusion and prejudice. This work sought to reflect on the power of performance, to modify the knowledge that artists and audience have about themselves and to act on the perception of the world that mobilizes subjects in their identity processes.